Common Perceptions about the Use of Fillers in Silicone Rubber Insulation Housing Composites - Refat Atef Ghunem; Yazid Hadjadj; Harold Parks (Energies, 2021)
This paper discusses the lessons learned about fillers that are added to silicone rubber insulation housing composites, in order to improve the erosion resistance against the dry-band arcing are presented and common perceptions. Common practices that employ alumina tri-hydrate are reviewed, including the additional influential effect of the water of hydration in the suppression of the dry-band arcing. The effect of the water of hydration is shown to be dependent on various factors, such as the hydrated filler level and the type of the hydrated filler. More recent paradigms in which hydrated fillers have not been employed are also reviewed. Volume and shield actions of fillers are essential aspects that need to be understood in the design of silicone rubber insulation housing composites for new applications such as HVDC. In addition, the thermal degradation mechanisms of silicone rubber and the corresponding suppression effects of the added fillers are summarized.